Evaluation of the “Sepekan” Application Utilization by the Gresik District Government - Kholifah, Anik Nur; Samsi, Nur; Widiyawati, Wiwik; Mulyani, Endah; Musfara, Deah Dwi; Indarto, Tomi (Journal of Nursing Science Update (JNSU), 2025)
Improvements in the utilization of the Sepekan application within the Gresik Regency are crucial to determining the extent of its proper implementation. This study aims to assess the usage of the "SEPEKAN" application, specifically regarding user discipline, in submitting final reports for completed activities. Sepekan is a web-based application designed to provide services to the Gresik community, particularly students, in connection with internship programs in the Gresik Regency. The sampling method employed in this study was total sampling. The respondents' ages ranged from 19 to 88 years, with the most significant representation coming from self-employed individuals, totalling 453 respondents. Subsequent analyses indicated a significant relationship between the purpose of using the website and user discipline, with a p-value of 0.00. Several facilitating factors or triggers for indiscipline were identified, notably variations in gender and age, which correlate with different levels of discipline. The results revealed that male users exhibited greater discipline compared to their female counterparts. At the same time, adolescents demonstrated higher levels of discipline among SEPEKAN users, although discipline also persisted among older individuals. Furthermore, there is a pressing need for enhanced communication, including cautionary messages through the web or stricter regulations for the timely submission of BAPPEDA files, to ensure the continuity of relevant agency agendas.